Valuation and holistic management of landscape heritage. Theoretical and practical agreements and disagreements - Ramírez Serpa, Iván (2018)
This article aims to be a reflective text, and to express, from an analytical, critical and practical approach to the notion of territory and cultural landscape, how said duality shapes the conception of heritage in a holistic way. Its goal is to show the decisiveness and inescapability the patrimonial component has for the purpose of the planning of territory, urban planning and sustainable development. The correlation and implication between theory and practice, and the comprehensiveness of the patrimonial component, are found through the examination of theoretical definitions, international agreements, management proposals and examples of practical cases in Peru. The reflection is set off by Ramón Folch’s statement, that "the landscape is the aspect of the territory and summarizes the history of the anthropic process that it has been able to develop". In such a way, the article interprets that the cultural landscape transmits and reflects the model of development established in a given territory, and its effect on heritage.